Rejecting unfairness enhances the implicit sense of agency in the human brain - Wang, Yuru; Zhou, Jiaxin (Scientific reports, 2024)
Sense of agency (SoA) describes the feeling of control over one’s actions and their consequences. One proposed index of implicit SoA is temporal compression, which refers to the phenomenon that voluntary actions and their outcomes are perceived as closer in time than they actually are. The present study measured temporal compression in the social norm violation situation. In two experiments participants joined in an Ultimatum game (UG), in which they were presented with offers that varied in fairness and they could choose to accept or reject the offers by pressing buttons. A neutral sound would occur after their choices in the UG and the participants had to estimate the time interval between their button pressing and the occurrence of the sound, and EEG signals were recorded during the task. Experiment 1 demonstrated that rejecting unfair offers decreased the perceived interval between action and outcome compared to accepting fair offers, suggesting a higher level of SoA after rejecting unfair offers. Experiment 2 replicated these results and further revealed an attenuated N1 in response to the sound following rejections of unfairness. Taken together, these results highlight the importance of social norms in affecting people’s behaviors and agency experiences.